2015
DOI: 10.1128/cvi.00402-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Adjuvant Effects of Type II Heat-Labile Enterotoxins in Combination with Two Different Candidate Ricin Toxin Vaccine Antigens

Abstract: Type II heat-labile enterotoxins (HLTs) constitute a promising set of adjuvants that have been shown to enhance humoral and cellular immune responses when coadministered with an array of different proteins, including several pathogen-associated antigens. However, the adjuvant activities of the four best-studied HLTs, LT-IIa, LT-IIb, LT-IIb T13I , and LT-IIc, have never been compared side by side. We therefore conducted immunization studies in which LT-IIa, LT-IIb, LT-IIb T13I , and LT-IIc were coadministered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The loss of epitopes corresponding to clusters III and IV, as well as to part of cluster II, explains why RVEc immunization results in a slight bias for antibodies against cluster I compared to RiVax (69). Nonetheless, in spite of lacking what are seemingly important neutralizing B cell epitopes, RVEc has proven as effective as RiVax at eliciting immunity to ricin in mice across a range of doses and with different adjuvants (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of epitopes corresponding to clusters III and IV, as well as to part of cluster II, explains why RVEc immunization results in a slight bias for antibodies against cluster I compared to RiVax (69). Nonetheless, in spite of lacking what are seemingly important neutralizing B cell epitopes, RVEc has proven as effective as RiVax at eliciting immunity to ricin in mice across a range of doses and with different adjuvants (69,70).…”
Section: Discussionmentioning
confidence: 99%
“…All vaccinated animals survived challenge, even groups that received only a prime boost regimen with the lowest dose of vaccine. Although RVEc was slightly more effective than RiVax at eliciting toxin-specific serum IgG titers and toxin-neutralizing activity (TNA) after only two immunizations, this trend was not apparent in a more recent study in which RiVax and RVEc were administered to mice by the intradermal routes [64]. While the two vaccines have not been tested head to head in the mouse model using the intramuscular route of vaccination to mimic the route by which the vaccines would be given to humans, there is no reason to expect that they would differ under such circumstances.…”
Section: Preclinical Studies Of Ricin Toxin Subunit Vaccines Rivamentioning
confidence: 99%
“…Investigations into the effects of different “next generation” adjuvants like AS01 on RiVax and RVEc is clearly warranted [75–77]. Towards this goal we recently demonstrated that LT-IIa and LT-IIb T13I , two related ADP-ribosylating enterotoxins from E.coli are potent adjuvants when combined with RiVax and RVEc and administered to mice by the intradermal route [64,78]. It remains to be determined whether either of these adjuvants is active in humans.…”
Section: F Key Challenges Moving Forward In Ricin Toxin Vaccine Devementioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Despite structural differences between these 2 subunit vaccines, headto-head comparisons have indicated that RiVax and RVEc when adsorbed to Alhydrogel or co-administered with LT-II adjuvants have identical capacities to induce neutralizing antibodies and to protect in mice. 12,13 No head-to-head comparisons have yet been attempted in non-human primates although intramuscular administration of RiVax adsorbed to aluminum hydroxide adjuvant protects rhesus macaques against the lethality of aerosolized RT.…”
Section: Introductionmentioning
confidence: 99%